Eksistensi Nahdlatul Ulama Dalam Meningkatkan Kualitas Pendidikan Islam Masyarakat Pesisir: Studi Di Pesisir Pantai Desa Kranji Kecamatan Paciran Kabupaten Lamongan - Ratih Kusuma Ningtyas (Darajat: Jurnal Pendidikan Agama Islam, 2018)
Nahdlatul Ulama is the largest Islamic community organization in Indonesia, Who is engaged in welfare community . Nahdlatul Ulama, which then we call NU. How not, in the Indonesian cultural culture this organization has become the front guard in guarding the world of religiosity or religious based education. So that as a consequence the problem of globalization is our shared responsibility, especially with its educational institutions and NU with the pesantren institutions. This research was carried out on the coast of Kranji village where NU was confronted with the condition of the people of Kranji who were famous for bad characters. This research focuses on how the role of the Nahdlatul Ulama in improving the quality of Islamic religious education in the coastal communities of Kranji village. Based on the type, this research is a qualitative descriptive study. Qualitative descriptive research is a study of certain phenomena or populations obtained by researchers from subjects in the form of individuals, organizations, or other perspectives. And this research uses a case study approach that is describing a background of certain objects or events in detail and depth. While data analysis is done using "inductive abstractive" logic data analysis, which is a logic that starts from "special to the public". The results of the study found that the role of Nahdlatul Ulama in improving the quality of Islamic religious education in coastal communities by means of cultural education in the form of religious activities in the community and structural education carried out in Islamic education institutions respectively.